Teaching effectiveness as perceived by the students and administrator in the secondary level at Maryknoll Academy - Panopio, Victor M. (Animo Repository, 1977)
1st work. Relatively in recent years, student evaluation of their teachers have gained acceptance in most colleges and universities, despite objections. Most administrative officers hear a great deal about the quality of teaching from students, faculty, and other administrative officers. Opinions about bad teaching are uniform and widespread, and the same is true of opinions in excellent teaching. Therefore, the purpose of this study is to discover if there is a significant relationship in the perception of teaching effectiveness by the student and the administrator. It seeks to investigate the qualities that students and administrators perceive in the faculty of Maryknoll Academy during the school year 1976-1977, and discover the hierarchy of their importance, which contributes to teacher effectiveness. It also sought to find significant relationship in the perception of teaching effectiveness by the administrator and each curriculum year. In addition, this research hopes to develop a valid and reliable instrument to measure teaching effectiveness. The Teacher Observation Inventory was used, as the instrument of the study. Responses to the TOI items were assigned numerical values or ratings according to the frequency of occurrences of the behaviors described in the items. Using the EMC-DLSU Coding Form, all the forms gathered and bundled according to teacher evaluated and year evaluating, were then tabulated. Using the Pearson r Coefficient of Correlation, the relationship between the two variables (students and administrator) was obtained. On the other hand, the relationship between the student and administrators perception of teacher effectiveness was obtained, using the Spearman Rohr Rank Order Correlation. -- 2nd work. The orientation of new faculty on campus appears to be a badly neglected administrative responsibility. Very few institutions operate formal orientation programs. Even fewer publish orientation handbooks. It is possible for a school to inform new faculty or remind seasoned veterans,